Echo and Irony: Weapons in Political Campaigns - Rut-Kluz, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The theory of relevance presented by Dan Sperber and Deidre Wilson (1995) is a general theory of communication which has been developing over the past decades and apart from the theoretical developments it has been implemented as a tool for various analyses of discourse. The aim of the paper is to present a relevance theoretic account of a special kind of attributive use of campaign material which was employed by candidates in TV advertisements for the US presidential election campaign in 2012. Candidates use this special kind, echoic use, implementing it not only to criticise the opponent but also to justify their negative attitude towards the material mentioned. Echoic use proves to be a powerful tool not only to criticise and maintain credibility, but also allow irony which seems to be, along with discrediting the rival, the most powerful weapon at a politician's disposal.
Keywords: relevance theory; attributive use; echoic use; TV campaign advertisements; US presidential election campaign